Discovering the Real World : Health Workers' Career Choices and Early Work Experience in Ethiopia - Serra, Danila (World Bank, 2012)
The Ethiopian health sector faces a number of challenges related to human resources, including geographical imbalances in the distribution of health workers, problems with job satisfaction, and a high willingness to migrate abroad. To address these challenges with appropriate policies, more empirical evidence is needed. The Ethiopian Health Workers Cohort Study was set up to produce evidence as input to policy design. To generate insights on health workers' career choices, preferences, and job satisfaction, the study followed the same health workers over time. The first wave of the study was conducted in April 2004 and surveyed 219 nursing students and 90 medical students who were in their final year of study. In the second wave of the survey, which took place between May and September 2007, researchers re-interviewed the nurses and the doctors, who had now entered the labor market. This paper reports the descriptive findings of the second wave as well as changes that were identified between the two survey rounds. The report is structured as follows. This chapter provides an overview of the Ethiopian health sector and a brief description of the survey methodology. Chapter two presents data on the health professionals' current activities, including the distribution of job functions across locations, sectors, and facilities. Chapter three summarizes the findings on job characteristics such as salaries and nonmonetary benefits; it also provides information about health professionals' level of satisfaction with job and life of and its evolution over time. Chapter four reports the results regarding health workers' willingness to work in rural areas, including an analysis of the evolution of reservation wages for work in a rural area, obtained from responses to contingent valuation questions. Chapter five focuses on the health worker's likelihood of migrating abroad in the near future, again using specially designed questions. Each chapter after chapter two starts with a summary of the pertinent results.